Preparation of N-Doped TiO2-ZrO2 Composite Films under Electric Field and Heat Treatment and Assessment of Their Removal of Methylene Blue from Solution - Lefu Mei; Ranfang Zuo; Jing Xie; Libing Liao; Hao Ding (Advances in Materials Science and Engineering)
TiO2-ZrO2 composite film with the grain size of 50 nm was synthesized by electric field and heat (EF&H) treatments. Portions of O atoms in the TiO2 network structure were replaced by N atoms as revealed by X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) analyses, suggesting formation of a nonstoichiometric compound TiO2-xNx on the composite film. The UV-Vis spectra of the film suggested that the visible light with wavelength of 550 nm could be absorbed for the N-doped composite film after EF&H treatment in comparison to a cutoff wavelength of 400 nm for the composite film without EF treatment. Photocatalytic experiments showed that the degradation rate of methylene blue by N-doped composite films increased significantly under visible light irradiation. The partial replacement of O by doped N played a very important role in narrowing the band gap and improving the visible light photocatalytic reactivity.